Interventions for smokeless tobacco use cessation. - Ebbert, J; Montori, V; Erwin, P; Stead, L (2011)
BACKGROUND: Use of smokeless tobacco (ST) can lead to nicotine addiction and long-term use can lead to health problems including periodontal disease, cancer, and cerebrovascular and cardiovascular disease. OBJECTIVES: To assess the effects of behavioural and pharmacologic interventions for the treatment of ST use. SEARCH STRATEGY: We searched the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, EMBASE, CINAHL, Web of Science, PsycINFO, Dissertation Abstracts Online, and Scopus. Date of last search: October 2010. SELECTION CRITERIA: Randomized trials of behavioural or pharmacological interventions to help users of ST to quit with follow up of at least six months. DATA COLLECTION AND ANALYSIS: Two authors independently extracted data. We summarised as odds ratios. For subgroups of trials with similar types of intervention and without substantial statistical heterogeneity, we estimated pooled effects using a Mantel-Haenszel fixed-effect method. MAIN RESULTS: Data from one study suggest that varenicline increases ST abstinence rates (Odds Ratio [OR] 1.6, 95% Confidence Interval (CI) 1.08 to 2.36) among Swedish snus users.Two trials of bupropion SR did not detect a benefit of treatment at six months or longer (OR 0.86, 95% CI 0.47 to 1.57). Nicotine replacement therapy (patch, gum, and lozenge) was not observed to increase tobacco abstinence rates (OR 1.14, 95% CI: 0.91 to 1.42). There was statistical heterogeneity among the 14 trials of behavioural interventions; seven of them reported statistically and clinically significant benefits, four suggested benefit but with wide CIs, whilst two had similar intervention and control quit rates and relatively narrow CIs. Heterogeneity was not explained by the design (individual or cluster randomization), whether participants were selected for interest in quitting, or specific intervention components. Most trials included either telephone counselling, an oral examination and feedback about any ST induced mucosal changes, or both. In a post-hoc subgroup analysis there was some evidence that behavioural interventions which include telephone counselling might increase abstinence rates more than interventions with less contact. In one trial an interactive website increased abstinence more than a static website. AUTHORS' CONCLUSIONS: Varenicline and behavioural interventions may help ST users to quit. Behavioural interventions incorporating telephone counselling or an oral examination are likely to increase abstinence rates.